THE 1958 NEW YORK CONVENTION IN INDONESIA: HISTORY AND COMMENTARIES BEYOND MONISM-DUALISM - Lumbantobing, John (UI Scholars Hub, 2019)
This Article recounts a complete history of Indonesia’s implementation of the 1958 NY Convention. In particular, the elaboration and analysis focus on the comparison between related provisions in the 1999 Indonesian Arbitration Law and the Convention’s provisions as well as on several key Indonesian court decisions on enforcement of foreign arbitral awards. Different than other writings in this area, this Article looks more closely at the practical issues which affect the way Indonesian courts apply or interpret the 1958 NY Convention, such as procedural hurdle and the judicial capacity to comprehend and understand basic concepts and principles of arbitration. The Article shows that those practical issues very much influence the implementation of the Convention in Indonesia while the courts oscillate between monism and dualism, and highlights the important role of doctrines in developing Indonesian jurisprudence on this area. In that vein, the conclusion here may also contribute in answering the wider question about the position of treaties under Indonesian law and how they are implemented in Indonesia beyond the superficial debate on monism-dualism.